Assessment of Wound-Healing Properties of Medicinal Plants: The Case of Phyllanthus muellerianus - Boakye, Yaw D.; Agyare, Christian; Ayande, George P.; Titiloye, Nicholas; Asiamah, Emmanuel A.; Danquah, Kwabena O. (Frontiers in Pharmacology, 2018)
Phyllanthus muellerianus (Family Euphorbiaceae), is a shrub which is widely distributed in West Africa and employed traditionally as a wound healing agent especially in Ghana. The aim of the study was to determine the in vivo wound healing activity of aqueous aerial part extract of P. muellerianus (PLE) and its major isolate, geraniin. Excision and incision wound models were used to determine the wound healing activity. Wounds were treated with PLE (0.25, 0.5 and 1% w/w) and geraniin (0.1, 0.2 and 0.4% w/w) aqueous creams. PLE and geraniin significantly (p<0.001) increased wound contraction rate and hydroxyproline production compared to untreated wounds. Histological studies of wound tissues showed high levels of fibroblasts and increased collagen content and cross-linking in PLE and geraniin-treated wound tissues. Immuno-histochemical investigations revealed high levels of TGF-β1 in PLE and geraniin-treated wound tissues compared to the untreated wound tissues. Tensile strength of incised wounds was significantly (p<0.05) high in PLE and geraniin treated wounds. PLE (0.1-100 μg/mL) significantly (p<0.001) reduce LDH release from HaCaT-keratinocytes compared to the untreated cells. PLE and geraniin possess wound healing and cytoprotective effect.